What senses do animals have? - Kalman, Bobbie (New York, NY : Crabtree Pub., 2009)
Just like people, animals also need to get information about their world. Like people, most animals also have the senses of sight, hearing, smell, taste, and touch, but their senses may be very different from a persons.
Our five senses -- Do animals have senses? -- How do animals see? -- Different kinds of eyes -- Whose eyes are these? -- Sense of smell -- Scents sent -- Smell and taste -- Touching information -- Hearing with ears -- Where are their ears? -- What is echolocation? -- Super senses -- Which sense is it? --
Includes index.
008-012.
Keywords: Senses and sensation -- Juvenile literature; Animal behavior -- Juvenile literature; Senses and sensation; Animal behavior